Kobiety w polityce aspiracje i praktyka - Górna-Kubacka, Anna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The paper discusses the role of women in public life, in particular in the realm of politics. Surveys show that women do well in free market economies, where they rank quite highly in the European Union (35% of employers), whereas their participation in politics is consider- ably smaller. The paper presents the data on women participating in the highest bodies of rep- resentational authorities and local governments, as well as their achievements in the Women’s Parliamentary Group and their struggle to obtain parity on electoral ballots, concluded by winning a 35% quota.
Women in Politics – Ambitions and Practice
Keywords: kobieta; polityka